Spacer acquisition from RNA mediated by a natural reverse transcriptase-Cas1 fusion protein associated with a type III-D CRISPR–Cas system in Vibrio vulnificus. Issue 19 (4th September 2019) - González-Delgado, Alejandro; Mestre, Mario Rodríguez; Martínez-Abarca, Francisco; Toro, Nicolás
Abstract: The association of reverse transcriptases (RTs) with CRISPR–Cas system has recently attracted interest because the RT activity appears to facilitate the RT-dependent acquisition of spacers from RNA molecules. However, our understanding of this spacer acquisition process remains limited. We characterized the in vivo acquisition of spacers mediated by an RT-Cas1 fusion protein linked to a type III-D system from Vibrio vulnificus strain YJ016, and showed that the adaptation module, consisting of the RT-Cas1 fusion, two different Cas2 proteins (A and B) and one of the two CRISPR arrays, was completely functional in a heterologous host. We found that mutations of the active site of the RT domain significantly decreased the acquisition of new spacers and showed that this RT-Cas1-associated adaptation module was able to incorporate spacers from RNA molecules into the CRISPR array. We demonstrated that the two Cas2 proteins of the adaptation module were required for spacer acquisition. Furthermore, we found that several sequence-specific features were required for the acquisition and integration of spacers derived from any region of the genome, with no bias along the 5′and 3′ends of coding sequences. This study provides new insight into the RT-Cas1 fusion protein-mediated acquisition of spacers from RNA molecules.